Unburnt areas in subtropical woodlands contain distinct reptile communities after extensive wildfire - Emery, Jon‐Paul; Doherty, Tim S.; Bruton, Melissa J.; Peck, Stephen; Maron, Martine (Austral ecology, 2024)
Extensive wildfires can have profound impacts on fauna communities by altering the vegetation structure and resource availability. However, unburnt areas within a fire mosaic may be important habitat for wildlife while the surrounding area recovers after fire. To understand the importance of unburnt vegetation for reptiles, we studied community assemblages at 15 burnt and 15 unburnt sites in a subtropical woodland 12 months after a 25 000 ha wildfire. We tested the relative importance of unburnt areas and structural attributes on reptile abundance, richness, and community composition across this landscape. Unburnt areas had higher species richness and diversity, but not overall abundance. Reptile community composition differed significantly between burnt and unburnt areas. Woody debris, which was retained in unburnt areas but depleted in burnt areas, was positively associated with increased reptile diversity and richness. Our results suggest that unburnt areas are vital for maintaining reptile diversity and richness within a woodland landscape after wildfire. These findings demonstrate the importance of ensuring fire management programs retain unburnt patches of vegetation in fire‐prone landscapes to sustain reptile communities. Following land‐scale wildfires, unburnt areas may provide critical areas for which wildlife including reptiles can recolonize the surrounding area. We examined the impact of approximately 12 months post wildfire in Western Queensland on reptile communities. We found that unburnt areas contained higher reptile richness, diversity and harboured distinctively different reptile communities from burnt areas. Our results suggest that unburnt areas are vital for maintaining reptile diversity and richness within a woodland landscape after wildfire.